Scopoletin potentiates the anti-cancer effects of cisplatin against cholangiocarcinoma cell lines (Bangladesh Journal of Pharmacology, 2015)
Chemotherapy with cisplatin in cholangiocarcinoma produces adverse effects and leads to resistance development by tumors. We aimed to evaluate anti-cancer effects by co-administration of cisplatin and scopoletin in cholangiocarcinoma cells. MTT assay, median effect principle, cell cycle arrest and apoptosis assay were conducted to determine anti-cancer effects. Results revealed that treatment with cisplatin and scopoletin resulted in dose-dependent reduction of cell viability for cholangiocarcinoma cells. Combination of these agents inhibited proliferation of cells significantly more than single agent either. Combination indices reflect additive cytotoxic effect, leading to >2 times dose reduction for each agent. Both the cell cycle arrest (G0/G1) and apoptosis induction underling the enhanced cytotoxicity for the combination. Besides, single agent conferred cell cycle arresting and apoptotic effects in cholangiocarcinoma cells. By contrast, non-cancer cells were less affected with combination. Our observations suggest that cisplatin and scopoletin combination may bring positive significance in cholangiocarcinoma treatment.